Computer-aided Drug Design: Innovation and its Application in Reshaping Modern Medicine - Gupta, Pooja; Chanana, Arsh; Kulkarni, Yukta R.; Narayan, Aditya; Shanker, Oma; Mahato, Bhabesh; Singh, Dharmendra; Patel, Akhilesh; Havelikar, Ujwal; Singh, Ravindra Pal; Chawra, Himmat Singh (Current Artificial Intelligence, 2024)
Computer-aided drug design has revolutionized the landscape of drug discovery, accompanied by a new era of innovation and efficiency of novel therapeutic agents. This article review explores the diverse innovations and practical applications that have propelled CADD into the forefront of modern medicine. CADD, a multidisciplinary field at the interaction of biology, chemistry, and computational science, offers a toolkit for the identification and development of pharmaceutical compounds. It has the ability to predict molecular interaction between drug and biological targets with remarkable precision, reducing the dependency on laborious and costly laboratory experiments. The review deals with two primary domains of CADD: structure-based and ligand-based design. This three-dimensional protein structure and screening of chemical libraries have led to rational changes. The analysis of known drug compounds' chemical and biological properties has enabled the creation of predictive models, opening new routes for drug discovery. The impact of CADD on the pharmaceutical industry is clear. This review highlights its instrumental role in the development of antiviral agents, cancer therapeutics, and treatment for various diseases. The transformation potential of CADD is not without challenges, including the need for substantial computational resources and the essential requirement of experimental analysis. The synergy between innovation and practical application is clear, driving unexpected efficiency and precision in the identification of therapeutic solutions. As pharmaceutical research continues to evolve, the role of CADD remains pivotal, assuring the rapid translation of scientific innovation into real-world medical advancements.
Keywords: Computer-aided drug design (CADD)